Tunability of Biodegradable Poly(amine-co-ester) Polymers for Customized Nucleic Acid Delivery and Other Biomedical Applications - Kauffman, Amy C. (Biomacromolecules, 2018)
Gene therapy promises to treat diseases that arise from genetic abnormalities by correcting the underlying cause of the disease rather than treating the associated symptoms. Successful transfer of nucleic acids into cells requires efficient delivery vehicles that protect the cargo and can penetrate the appropriate cellular barriers before releasing their contents. Many viral vectors and synthetic polycationic vectors for nucleic acid delivery do not translate well from in vitro to in vivo applications due to their instability and toxicity. We synthesized and characterized a library of biocompatible low charge density polymers from a family of poly(amine-co-ester) (PACE) terpolymers produced via enzyme catalyzed polymerization. PACE polymers are highly customizable; we found that the terpolymer composition can be optimized to produce efficient transfection of various nucleic acids—including DNA plasmids, mRNA, and siRNA—in specific cell types with low toxicity. Our findings suggest that the unique tunability of PACEs offers new tools for gene therapy and other biomedical applications.